Enhancing Traditional Market Viability: A Case Study of Revitalizing Sleko Market - Gregorius Adiwidharta; Theresia Liris Windyaningrum; Chatarina Dian Indrawati (Universitas Muhammadiyah Sidoarjo, 2023)
This study addresses the imperative of adapting traditional markets to evolving consumer demands for sustained economic development. Focusing on Sleko Market in Madiun City, we propose a revitalization strategy guided by pertinent regulations and standards. Through questionnaire surveys and the Preference Selection Index (PSI) method, three pivotal indicators—multiuse space availability, streamlined loading/unloading zones, and effective advertising infrastructure—were identified. Our findings underscore the need for improved market design aligned with urban regulations and health guidelines, contributing to the quality enhancement of traditional markets. Highlight: Adapting to Consumer Demands: This study emphasizes the necessity of aligning traditional markets with evolving consumer preferences to ensure sustainable economic growth. Revitalizing Sleko Market: Focusing on Sleko Market in Madiun City, the research proposes a strategy for revitalization, guided by relevant regulations and standards. Enhancing Market Quality: Through surveys and the PSI method, crucial indicators like multiuse space, loading/unloading zones, and advertising infrastructure are identified, underscoring the significance of improved market design in compliance with urban regulations and health guidelines. Keyword: Traditional Markets, Consumer Demands, Revitalization Strategy, Urban Regulations, Market Design